Optimization of the Dikyasa Sat Lantas Unit in Overcoming Congestion at the Tanjungsari Market, Jurisdiction Area of Sumedang Police - Budiman, Muchamad Arif (Indonesian Journal of Police Studies, 2024)
The background of this study is the status of traffic congestion that has never been resolved. From a very strategic geographical location, Sumedang Regency is a southern route to Central Java Province, and also has a Cileunyi Toll Road. Therefore, Sumedang Regency has a very good activity. The Sumedang Regional police station has taken steps to prioritize the Traffic Technical Unit especially the Dikyasa Unit to replace some of the traffic jams. The Sumedang Police Station then made efforts to support the problem of traffic congestion through the active role of the community in order to take order to pass through traffic. The purpose of this study is to explain the picture of congestion in the Tanjungsari Sumedang Market, To provide an overview of the activities carried out by the Sumedang District Traffic Unit Unit in the execution of packaging at the Tanjungsari Sumedang Market, to explain what data are questioned by the Traffic Unit Unit of the Sumedang District Police Unit in ties in traffic jams in the Tanjungsari Sumedang market. Researchers used several theories, namely management theory, role theory, the concept of traffic smoothness, the concept of traffic regulation, the concept of congestion, the concept of public management, the concept of management and traffic engineering. In this study using qualitative methods and the methods used are field research and data collection techniques by interviewing, observing, and studying documents. Internal and external factors that influence it affect it. There are several things that must be done, (1) following the members, (2) fixing the organizing of personnel in units of traffic units, (3) making innovations in the Traffic Engineering project, (4) improving the performance of Traffic Sumedang Police Dikyasa members in overcoming congestion problems in Sumedang Regency.